Anterograde Trafficking of G Protein-Coupled Receptors: Function of the C-Terminal F(X)(6)LL Motif in Export from the Endoplasmic Reticulum - Duvernay, Matthew T. (American Society for Pharmacology and Experimental Therapeutics, 2009)
We have reported previously that the F(X)(6)LL motif in the C termini is essential for export of α(2B)-adrenergic (α(2B)-AR) and angiotensin II type 1 receptors (AT1Rs) from the endoplasmic reticulum (ER). Here, we further demonstrate that mutation of the F(X)(6)LL motif similarly abolished the cell-surface expression of α(2B)-AR, AT1R, α(1B)-AR, and β(2)-AR, suggesting that the F(X)(6)LL motif plays a general role in ER export of G protein-coupled receptors (GPCRs). Mutation of Phe to Val, Leu, Trp, and Tyr, and mutation of LL to FF and VV, markedly inhibited α(2B)-AR transport, indicating that the F(X)(6)LL function cannot be fully substituted by other hydrophobic residues. The structural analysis revealed that the Phe residue in the F(X)(6)LL motif is buried in the transmembrane domains and possibly interacts with Ile58 in β(2)-AR and Val42 in α(2B)-AR, whereas the LL motif is exposed to the cytosolic space. Indeed, mutation of Ile58 in β(2)-AR and Val42 in α(2B)-AR markedly disrupted cell surface transport of the receptors. It is noteworthy that the Val and Ile residues are highly conserved among the GPCRs carrying the F(X)(6)LL motif. Furthermore, the Phe mutant exhibited a stronger interaction with ER chaperones and was more potently rescued by physical and chemical treatments than the LL mutant. These data suggest that the Phe residue is probably involved in folding of α(2B)-AR and β(2)-AR, possibly through interaction with other hydrophobic residues in neighboring domains. These data also provide the first evidence implying crucial roles of the C termini possibly through modulating multiple events in anterograde trafficking of GPCRs.